Insights from tissue "omics" analysis on intestinal remodeling in celiac disease. Issue 23 (25th October 2021) - Stamnaes, Jorunn
Abstract: Celiac disease (CeD) is a prevalent intestinal disorder that only develops in genetically susceptible individuals when they mount a harmful CD4+ T‐cell response towards gluten peptides. Intake of gluten leads to inflammation and remodeling of the small intestine with symptoms such as nausea and diarrhea. The only current treatment is a lifelong gluten free diet. The immunological basis for CeD is well characterized but the mechanisms that drive intestinal remodeling are still poorly understood. Transcriptome or proteome analysis of intestinal biopsies gives a global snapshot of all processes that occur in the tissue, including alterations in the epithelial cell layer. This paper will introduce concepts of intestinal remodeling, recapitulate the current understanding of CeD pathogenesis and discuss findings from relevant tissue "omics" studies. On the basis of this review, I give perspectives on what tissue "omics" studies can tell us about disease pathogenesis with a particular focus on the gluten induced intestinal remodeling.